Evaluation of the predictive value of the bleeding prediction score VTE‐BLEED for recurrent venous thromboembolism. Issue 3 (25th May 2019) - Klok, Frederikus A.; Presles, Emilie; Tromeur, Cecile; Barco, Stefano; Konstantinides, Stavros V.; Sanchez, Olivier; Pernod, Gilles; Raj, Leela; Robin, Philippe; Le Roux, Pierre‐Yves; Hoffman, Clément; Mélac, Solen; et al.
Abstract: Introduction: VTE‐BLEED is a validated score for identification of patients at increased risk of major bleeding during extended anticoagulation for venous thromboembolism (VTE). It is unknown whether VTE‐BLEED high‐risk patients also have an increased risk for recurrent VTE, which would limit the potential usefulness of the score. Methods: This was a post hoc analysis of the randomized, double‐blind, placebo‐controlled PADIS‐PE trial that randomized patients with a first unprovoked pulmonary embolism (PE) initially treated during 6 months to receive an additional 18‐month of warfarin vs. placebo. The primary outcome of this analysis was recurrent VTE during 2‐year follow‐up after anticoagulant discontinuation, that is, after the initial 6‐month treatment in the placebo arm and after 24 months of anticoagulation in the active treatment arm. This rate, adjusted for study treatment allocation, was compared between patients in the high‐ vs. low‐risk VTE‐BLEED group. Results: In complete case analysis (n = 308; 82.4% of total population), 89 (28.9%) patients were classified as high risk; 44 VTE events occurred after anticoagulant discontinuation during 668 patient‐years. The cumulative incidence of recurrent VTE was 16.4% (95% confidence interval [CI], 10.0%‐26.1%; 14 events) and 14.6% (95% CI, 10.4%‐20.3%; 30 events) in the high‐risk and low‐risk VTE‐BLEED groups, respectively, for an adjusted hazard ratio of 1.16 (95% CI, 0.62‐2.19). Conclusion: In this study, patients with unprovoked PE classified at high risk of major bleeding by VTE‐BLEED did not have a higher incidence of recurrent VTE after cessation of anticoagulant therapy, supporting the potential yield of the score for making management decisions on the optimal duration of anticoagulant therapy.